Assessment of rotahaler inhalation technique and determinants of incorrect perfomance among COPD clients in DH, KUTH. - Sapkota, Diksha (2009)
ABSTRACT: This study entitled "Assessment of Rotahaler Inhalation Technique and Determinants of Incorrect Performance among COPD clients in KUTH, DH" was conducted with objective to find out the rotahaler usage techniques among the COPD clients and the factors affecting the performance. A descriptive cross sectional study was carried out among the 100 COPD clients, inpatients and outpatients attending DH ( mean age 63.44+-9.73,59 female and 41 male) using the observational checklist and interview. Descriptive statistics such as frequency distribution and percentage were used for presenting the socio-demographic data and chi-square test was used to find out the association between various factors and inhalation technique. Results revealed that 37% percentage of the respondents demonstrated the correct technique and 67% had incorrect technique. Regarding the common mistakes during inhalation, majority 59% of the respondents failed to hold the breath, 25% of respondents were unable to breathe in through the mouth deeply and 25% exhale into the device. Educational level, occupational activities and re-demonstration of the technique by respondents were found to be the factors affecting performance (p <0.05) while this study couldn't establish the relationship between the correct performance and age ( above 60yrs and below 60yrs), gender (male and female), duration of use (more than a year and less than a year) and had demonstration of technique and teaching at follow up visits as p>0.05. This study concludes that the majority of the respondents had incorrect technique to health education program targeting the errors identified should be carried out. Respondents should be carefully instructed on its correct use and arrangements should be made for regular follow up to ensure good inhaler technique. This would lead to a greater clinical response and improved patient compliance. Keywords: COPD, dry powder inhaler, rotahaler, inhalation technique